Religious Values as Social Capital for Micro, Small and Medium Enterprises Facing Crisis in Kediri City - Ningtyas, Trimurti; Saadati, Lailis Nur; Istoni, Nabilla Meyvi (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2025)
This study investigates the role of religious values as a form of social capital in supporting the resilience of micro, small, and medium enterprises (MSMEs) during the COVID-19 pandemic in Kediri City, Indonesia. Using a qualitative approach, data were collected through in-depth interviews with eight MSME owners who managed to maintain their businesses throughout the crisis. The findings reveal that religious experiences and beliefs foster resilience and adaptability by encouraging persistence, community engagement, and mutual support. MSME owners relied on religious communities not only for spiritual guidance but also as practical networks for business adaptation. This study highlights the importance of integrating religious values into the conceptualization of social capital, suggesting that faith-based networks provide both psychological and material resources for business survival in times of crisis. The research offers new insights for policymakers and practitioners aiming to enhance MSME resilience through community-based and religiously-informed approaches.